A Analisis Kessalahan Mahasiswa Dalam Menyelesaikan Soal Barisan Monoton Dengan Perspektif Teori Kastolan - Nainggolan, Gustia Louisa; Siregar, Dea Athalia; Dhuha, Nadira Kaylana; Sinurat, Putra Paulus; Simanullang , Michael Christian (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze the types of errors made by students in solving problems involving Monotonic Sequences, using Kastolan’s error theory as the analytical framework. A qualitative descriptive approach was adopted, involving three students from a Mathematics Education Study Program as research participants. Data were collected through problem-solving tasks distributed via Google Forms and analyzed based on Kastolan’s error categories. The data analysis process consisted of three stages: data reduction, data presentation, and conclusion drawing. The findings revealed that procedural errors were the most dominant, occurring in 66% of the responses and classified as very high. Conceptual errors followed with a percentage of 33%, categorized as moderately high. Technical errors appeared least frequently, with a percentage of 11%, and were categorized as low. These results indicate that students face difficulties in following systematic steps during problem-solving. Therefore, educators are encouraged to reinforce students’ procedural skills by implementing learning strategies that are more structured, focused, and effective.